2022
DOI: 10.3390/su14137655
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Campus Experience in a Post-COVID World: A Multi-Stakeholder Design Thinking Experiment

Abstract: In a post-COVID world, rethinking the campus experience is critical for defining new pedagogical strategies. As higher education moves toward more student-centred action learning models, university leaders should engage in democratic design methods that empower students and professors. Design thinking (DT) is a user-centred design approach that can aid in the creation of future learning environments. While DT has been used in innovative space design, we know little about how students, professors, and other com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Given the insights generated at each stage of the DT application (inspire, ideate, and implement) [48], the authors demonstrated the importance of this application for transforming cities, neighborhoods, and regions into smarter and more sustainable ones. The most significant contributions of this application to smart cities can be highlighted below:…”
Section: Discussion and Learnings With The Software Tool Developed Wi...mentioning
confidence: 99%
“…Given the insights generated at each stage of the DT application (inspire, ideate, and implement) [48], the authors demonstrated the importance of this application for transforming cities, neighborhoods, and regions into smarter and more sustainable ones. The most significant contributions of this application to smart cities can be highlighted below:…”
Section: Discussion and Learnings With The Software Tool Developed Wi...mentioning
confidence: 99%
“…Prototyping is the fourth stage to capture the solution at a glance, so it should be shown in the form of a mock-up or design that visualizes the solution required by the user [34]. To achieve a good prototype, the team should use specific design tools or sketches to show the solution [35].…”
Section: Design Thinkingmentioning
confidence: 99%
“…This increased the workload for teachers, who were under great pressure to redesign subjects and infrastructures [79]; however, remote learning is a necessity in times of lockdowns [81], preventing students from experiencing setbacks during school closures [82]. In this regard, COVID-19 has implied the opportunity to adopt remote learning, making the education system immersed in a substantial change toward new teaching and learning models [81,83,84] more student-centered [32]. In addition, according to Foo et al [85], new teaching and learning models should not be limited to crisis situations; it is necessary to learn about them to ensure sustainable education and face future and uncertain challenges.…”
Section: Design Project Management Challenge In Remote Learningmentioning
confidence: 99%
“…One of the knowledge areas that positively influence the development of these skills and on which this article focuses is the design field and Design Thinking (DT) in its broadest sense [27][28][29][30][31]. DT consists of the formulation and resolution of complex problems through a creative human-centered process [27,28], being suitable for challenges characterized by a high level of uncertainty, such as most sustainability-related problems [32]. Thus, DT provides a framework (i.e., an innovation approach) for sustainability-oriented innovation (i.e., an innovation outcome) [33].…”
Section: Introductionmentioning
confidence: 99%